PREY SELECTION IN CARP (CYPRINUS CARPIO L. 1758) LARVAE - BAMBROO, P; SHARMA, KULDEEP K (Journal of the Inland Fisheries Society of India, 2021)
Prey selectivity pattern was tested in carp (Cyprinus carpio L.) larvae from the initiation of exogenous feeding up to the age of 40 days (25mm) using Ivlev’s Electivity Index ‘E’ and Bartell’s Size Selection Index ‘S’. The larvae were found to be particulate planktivores from day first of exogenous feeding. Strong foraging preference was shown by larvae for slow moving cladocerans during very early days of life, while evasive copepods were included in the diet from 10th day of age. Ceriodaphnia reticulata was found to be the most preferred food organism of larvae at the commencement of exogenous feeding up to the age of 18 days. The first feeding larvae are gape–limited and show preference for smaller prey than the average size available. The advanced stages of larvae through fry have shown active preference for large prey. However, this preference is dynamic as range of prey size increased with age. Key words : Carp larvae, foraging preference, Ceriodaphnia, particulate planktivores, gape - limited